Software testing for wireless mobile computing. - Satoh, I.
4G wireless networks make it increasingly difficult to develop and test application software for mobile terminals in comparison with 3G or earlier generations. These 4G networks incorporate wireless LAN technologies, and mobile terminals can access the services provided by LANs as well as global network services. Therefore, software running on mobile terminals may depend on not only its application logic but also on services within the LANs to which the terminals are connected. To construct correct software to run in mobile terminals for 4G wireless networks and wireless LANs, it must be tested in all the networks to which the terminal could be moved and be connected. This article presents a new approach, called flying emulator, to testing software designed to run on mobile terminals. Like existing approaches, the approach provides software-based emulators of its mobile terminals for software designed to run the terminals. It is unique because it constructs emulators as mobile agents that can travel between computers. These emulators can carry the target software to the networks to which the terminals are connected and allow it to access services provided by the networks in the same way as if it was moved with and executed on the terminals connected to the networks. This article describes the idea of the approach, its implementation, and our experience with a typical application.
Keywords: 4G wireless networks; Flying emulator; Global network services; Mobile agents; Mobile terminals; Software testing; Software-based emulators; Wireless LAN technologies; Wireless mobile computing